2021
DOI: 10.3390/ijerph18157804
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Quality of Life of Elderly Women with Fall Experiences

Abstract: This study aimed to describe the health-related quality of life of elderly women with experience in fall treatment as well as to prepare basic data for the development of interventions to improve the quality of life for this group. The study was based on raw data from the 2019 Korea Community Health Survey. Using the SPSS program, the characteristics of the subjects were tested by frequency, percentage, and chi-square test. To establish the impact of fall experience on the health-related quality of life of eld… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 27 publications
3
11
0
1
Order By: Relevance
“…It was reported that elderly people with chronic diseases had a lower QoL following a fall than elderly people without chronic diseases [13,14]. The present study was consistent with previous research.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…It was reported that elderly people with chronic diseases had a lower QoL following a fall than elderly people without chronic diseases [13,14]. The present study was consistent with previous research.…”
Section: Discussionsupporting
confidence: 93%
“…One study found that the post-fall QoL for elderly people living with their spouses was high [14]. The present study was consistent with previous research.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Hence, there is the tendency of changes in sleep patterns to result in psychological exhaustion and a feeling of mental fatigue which, in turn, may impair socialization, subjective well-being and quality of life. In Korea, old women who kept a sleep duration longer than 8 hours per night were related to better scores for HRQoL than those with less sleep hours 40 .…”
Section: Discussionmentioning
confidence: 93%